2018
DOI: 10.1016/j.jsat.2018.06.006
|View full text |Cite|
|
Sign up to set email alerts
|

A sequential analysis of motivational interviewing technical skills and client responses

Abstract: Background: The technical hypothesis of Motivational Interviewing (MI) proposes that: (a) client talk favoring behavior change, or Change Talk (CT) is associated with better behavior change outcomes, whereas client talk against change, or Sustain Talk (ST) is associated with less favorable outcomes, and (b) specific therapist verbal behaviors influence whether client CT or ST occurs. MI consistent (MICO) therapist behaviors are hypothesized to be positively associated with more client CT and MI inconsistent (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…For example, one study has found that affirming statements made by the therapist is the only MICO response which both increased change talk and decreased sustain talk in the context of reducing hazardous drinking in a student population [ 53 ]. A second study has shown that open questions and complex reflections are associated with changes from sustain talk and change talk (and vice versa) compared to simple reflections and paraphrasing [ 54 ]. Similarly, aggregate measures of change and sustain talk may contain subtypes of language that are differentially related to outcome following MI [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study has found that affirming statements made by the therapist is the only MICO response which both increased change talk and decreased sustain talk in the context of reducing hazardous drinking in a student population [ 53 ]. A second study has shown that open questions and complex reflections are associated with changes from sustain talk and change talk (and vice versa) compared to simple reflections and paraphrasing [ 54 ]. Similarly, aggregate measures of change and sustain talk may contain subtypes of language that are differentially related to outcome following MI [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the relationship between an elicitation and its response may partially be a function of the state of the conversation prior to the elicitation. Future research would do well to take this possibility into account, although recent findings indicate that some clinician elicitations may actually have the effect of breaking such momentum and shifting the direction of discussion (Laws et al, 2018). Another limitation is the assumed directionality of the present analyses, which emphasized the effect of the clinician on the client even though a conversation is a bidirectional phenomenon.…”
Section: Limitationsmentioning
confidence: 85%
“…Also, the interaction of client and therapist behaviors (i.e. sequential analysis) has been studied using MI concepts ( Apodaca et al, 2016 ; Berman et al, 2019 ; Drage et al, 2019 ; Laws et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%